Striding Towards Harmony: Research-Based Learning in Islamic Religious Education to Strengthen Washatiyah Islamic Values - Bahri , Rosidi; Kholis , Nur; Bakar , Yunus Abu (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
The attitude of intolerance and rejection of diversity in the school environment and students is based on a narrow religious understanding and mono interpretation. Islamic Religious Education (PAI) learning, which is actually expected to be able to instil the values of Washatiyah Islam, has actually become a trigger for the entry of narrow religious views and understandings. This research seeks to discuss how PAI learning is conducted, with a Research Based Learning (RBL) approach so that the assessment can instil the values of Wahatiyah Islam. The research method was conducted through Systemetical Literature Review (SLR) using the Publish or Perish application as an identification instrument for journal articles. The articles obtained were evaluated based on the criteria of quality, novelty, and suitability to the specific research theme. The results showed that the values of Washatiyah Islam can be instilled in students through the RBL approach in PAI learning. The RBL approach is able to open students' religious thinking horizons widely through critical, analytical and collaborative learning. The RBL approach in PAI learning requires commensurate collaboration between teachers and students in order to get maximum results, especially in instilling the values of Wasshtiyah Islam